АКУМУЛЯЦІЯ ВАЖКИХ МЕТАЛІВ В ЕКОСИСТЕМАХ СОСНОВИХ ЛІСІВ В УМОВАХ ЗАБРУДНЕННЯ АТМОСФЕРИ ВИКИДАМИ ТЕС - Voron, V. P. (Ukrainian Research Institute of Forestry and Forest Melioration named after G. M. Vysotsky (URIFFM), 2018)
Introduction Thermal power plants are a powerful source of atmospheric pollution by phytotoxicants, including heavy metals. During coal burning, heavy metals with ash, which accounts for up to 40 % of the emissions of Zmiyiv Thermal Power Plant, is carried through the pipes into the atmosphere. The release of emissions into the atmosphere is the primary cause of pollution and negative changes not only in an aerotope (air, precipitation) but also in a trophotope (litter and soil). Materials and Methods Heavy metals accumulation was studied in various components of ecosystems in pine forests of the industrial zone of Zmiyiv Thermal Power Plant The studies were based on methods of comparative ecology. The sample plots were located on the ecological profile on 4 to 28 km from the Zmіyiv Thermal Power Plant. The concentration index (Іc) was defined as the ratio of the element content in the investigated object to its content in the control. Results The lowest value of the heavy metal ions concentration index (1.45) was found in soils. The range of concentration indices for many heavy metals is not high. The greatest increase in concentration indices is peculiar for Mn, Ni (up to 2.5), Cu (7.5 times), Pb (up to 10). The highest level of pollution is typical for 3–5 km zone around Zmiyiv Thermal Power Plant, and the maximum is for the forest edges facing it. However, there is no clear dependence of the heavy metals content on the distance to the Thermal Power Plant because their content is high in the peripheral zones also due to the transfer of light ash particles to a considerable distance from the source of contamination. For the content in the soil, heavy metals are arranged in the following order: Ti > Mn > Zn > Cr > Ni > V > Cu > Pb > Co. Needle rank second in the level of heavy metals accumulation. For it, the concentration indices of heavy metals are 1.60–2.45. The highest ash and heavy metals contents are in the most polluted part of forests in the Serbovka area, and the maximum is on the forest edge, which is directed towards the Thermal Power Plant. In the technogenic zone, the ash and heavy metals content in the needles increases with aging. The ratio between the content of heavy metals in 2- and 1-year-old needles increases, while for 3- and in 2-year-old needles, it, vice versa, decreases as getting close to Zmiyiv Thermal Power Plant. This is explained by the fact that the needle packing of the third-year-old shoots is less than that of the second due to premature defoliation. And since pine needles that have accumulated a lethal dose are falling, the level will decrease in 3-year-old needles. The litter has the highest level of relative accumulation. The ash content in the litter is much higher than in the needles. So, in the technogenic zone, the ash content of the top layer of the litter is 1.3–2.0 times greater than in the needles. The indices of heavy metals concentration in the lower layer of the litter are also higher than in the soil. The especially significant growth of indices of heavy metals concentration at the lower layers of the litter is characteristic for pine forests located near the Thermal Power Plant. The heavy metals concentration indices increase down the litter profile. They are maximum for H/F. With the exception of copper and cobalt, the content of heavy metals in the upper layer of the litter is significantly higher than that in the needles of the third year: 2–5 times for chromium, 1.6–2.0 times for zinc, 1.6–3.0 times for lead. That is, the main source of contamination of the litter is not the intake of heavy metals with the mortmass of the needles, but their sedimentation with ash on the earth's surface. The obtained data on the mortmass reserves of the litter allowed determining the value of the total pollution of this ecosystem component. The proportion of heavy metals increases downward along the litter profile. The extremely big difference is between the litter and humus layers of the litter. Heavy metals storage in the H layer is tens or even hundreds of times larger than in the L layer.